Optical Indoor Positioning System Based on TFT Technology - Gőzse, István (Sensors (Basel), 2015)
A novel indoor positioning system is presented in the paper. Similarly to the camera-based solutions, it is based on visual detection, but it conceptually differs from the classical approaches. First, the objects are marked by LEDs, and second, a special sensing unit is applied, instead of a camera, to track the motion of the markers. This sensing unit realizes a modified pinhole camera model, where the light-sensing area is fixed and consists of a small number of sensing elements (photodiodes), and it is the hole that can be moved. The markers are tracked by controlling the motion of the hole, such that the light of the LEDs always hits the photodiodes. The proposed concept has several advantages: Apart from its low computational demands, it is insensitive to the disturbing ambient light. Moreover, as every component of the system can be realized by simple and inexpensive elements, the overall cost of the system can be kept low.